1996
DOI: 10.1093/nar/24.21.4185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rat Class 3 aldehyde dehydrogenase gene promoter

Abstract: The Class 3 aldehyde dehydrogenase gene (ALDH-3) is differentially expressed. Expression is either constitutive or xenobiotic inducible via an aromatic hydrocarbon (Ah) receptor-mediated pathway, depending upon the tissue. A series of studies were performed to examine the regulation of rat ALDH-3 basal expression. DNase I footprint analysis identified four DNA regions within the proximal 1 kb of the 5' flanking region of rat ALDH-3 which interact with regulatory proteins. Reporter gene and gel mobility shift a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…DNase I footprinting experiments indicate that AP1 and Sp1 are involved in expression of the rat ALDH3 gene in hepatoma cells (35). AP2 and Sp1 are involved in the regulation of keratin gene expression in the cornea.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…DNase I footprinting experiments indicate that AP1 and Sp1 are involved in expression of the rat ALDH3 gene in hepatoma cells (35). AP2 and Sp1 are involved in the regulation of keratin gene expression in the cornea.…”
Section: Resultsmentioning
confidence: 96%
“…Although cultured hepatoma cells have been used to study induced expression of the rat ALDH3 gene (33)(34)(35), examination of available primary and simian virus 40-transformed corneal epithelial cells showed that the endogenous ALDH3 gene is not expressed in cultured corneal cells (data not shown). Similarly, ALDH3 activity declines in intact rat corneas placed in culture (25).…”
Section: Resultsmentioning
confidence: 99%
“…A series of deletion mutants of the proximal 5Ј-flanking region of aldh3 were prepared by polymerase chain reaction as described previously (6), namely pI-3, pI-4, pI-5, pI-6, and pI-8. Construct p⌬(Ϫ1054/Ϫ392)ALDH was produced by treating pALDH3.5 with the restriction enzyme PstI to remove a portion of the flanking region from Ϫ1057 bp to Ϫ392 bp relative to the transcription start site; the resulting plasmid was gel purified and religated to yield p⌬(Ϫ1057/Ϫ392)ALDH.…”
Section: Methodsmentioning
confidence: 99%
“…The data shown are representative of three separate experiments where the effect of the H8 was to cause a 2.7-3.0-fold increase in aldh3 mRNA levels; dibutyryl cAMP (DiBC) or forskolin (FOR) decreased both BA induction and the H8 potentiation of BA induction by 60 -75%, in all cases. (1,5,6,30) have developed a highly inducible 5Ј-flanking construct containing 3.5 kb of upstream sequence of the rat aldh3 gene in a chloramphenicol acetyltransferase (CAT) reporter gene. Basal level expression of this gene is cell type-specific, and liver displays very low basal expression (1, 2).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation